Reconstruction of Gender-Fair Child Protection from an Islamic Law Perspective - Siti Aulya Indira; Hawa; Kurniati (PT. Nawa Edukasi Nusantara, 2026)
Several classical Islamic legal regulations related to child protection still exhibit patriarchal tendencies, which can lead to gender inequality. This is evident in aspects such as the distribution of custody rights (hadhanah), the obligation to provide for children, and the decision-making process that affects children's lives, which are often based on literal interpretations of texts without considering the essence and universal objectives of sharia (maqashid al-syari'ah). Therefore, this research aims to reconstruct the concept of gender just child protection within the framework of Islamic law. Methodologically, this research is a library research study with a qualitative approach oriented towards philosophical- normative analysis. Primary data sources include authoritative texts of the Qur'an and Hadith, as well as classical and contemporary works of Islamic jurisprudence, while secondary sources are obtained from academic literature related to gender studies, Islamic family law, and maqashid al-syari'ah. The data analysis technique was carried out through two main stages: thematic content analysis to identify prevailing legal discourse patterns, followed by critical-reflective analysis using the maqashidiyah approach to evaluate and reconstruct these concepts. The research findings reveal that several conventional fiqh constructions regarding child protection tend to ignore the principle of substantive justice, particularly in the establishment of rigid gender roles. As an alternative, this study reconstructs the concept of gender-just child protection through a reinterpretation of the hadhanah institution as a collective responsibility (takaful) based on the principle of the benefit of the child (maslahat al-thifl).